Quality Management and Higher Education: Big-Q, Little-q, Leadership, and Culture - Luoma, Keith (Journal of Applied Business and Economics, 2024)
Quality management is a philosophy that seeks to improve excellence in products, services, processes, and people. Quality management is more than a collection of tools and techniques. At its heart, it offers a different way of thinking about the organization, one that offers a unifying culture. Quality management has been successfully applied in manufacturing, service, healthcare, and a host of other fields, but applications to higher education have been comparatively limited. In this paper we distinguish between Big-Q (characterized by an overarching quality management system) and Little-q (a projects-based approach). We apply Deming’s 14 points to higher education leadership and culture, and we report on a case study which illustrates these principles in action.